2007
DOI: 10.1167/iovs.07-0588
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Pathogen or Commensal: A PCR-Based Study of Surface Bacterial Flora in Normal and Dry Eyes

Abstract: Molecular analysis revealed a diverse ocular surface bacterial population. In addition to the normal flora, various potentially pathogenic bacteria were identified. The detection of known pathogens in both normal and dry eyes, with minimal signs of infection, presents a diagnostic dilemma. It remains unknown whether their presence is associated with inflammation and reduced goblet cell density or whether they adversely affect the ocular surface predisposing it to abnormal microbial colonization. In the absence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
214
1
7

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 275 publications
(250 citation statements)
references
References 49 publications
12
214
1
7
Order By: Relevance
“…It belongs to the Nocardioform group of the aerobic actinomycetes, which also includes genera such as Nocardia and Mycobacterium [2]. Recently Rhodococcus erythropolis has been identified as part of the regional microflora of individuals with normal and dry eyes [4]. The importance of this finding is uncertain, although there is a case report of Rhodococcus erythropolis endophthalmitis after lens implantation [10].…”
Section: Discussionmentioning
confidence: 99%
“…It belongs to the Nocardioform group of the aerobic actinomycetes, which also includes genera such as Nocardia and Mycobacterium [2]. Recently Rhodococcus erythropolis has been identified as part of the regional microflora of individuals with normal and dry eyes [4]. The importance of this finding is uncertain, although there is a case report of Rhodococcus erythropolis endophthalmitis after lens implantation [10].…”
Section: Discussionmentioning
confidence: 99%
“…Significant differences were found between the results of microbiological analysis of ocular fluorescence and results of conventional culture methods using metagenomic approaches (12)(13)(14). In a study using traditional culture methods, only Staphylococcus and Bacillus species were detected.…”
Section: Introductionmentioning
confidence: 94%
“…Some studies have shown a more intense bacterial burden in the eyes of patients with Sjogren's syndrome than in the eyes of healthy volunteers (13,37). Genetic analyses may reveal details of ocular surface problems and ocular microbiota associations.…”
Section: Comparison Of Ocular Microbiota With Other Mucosal Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the body are several characterized microbiomes, including that of the distal gut (Eckburg et al 2005;Qin et al 2010), vaginal mucosa (Oakley et al 2008;Fredricks et al 2009), oral mucosa (Aas et al 2005;Keijser et al 2008;Nasidze et al 2009a;Nasidze et al 2009b;Zaura et al 2009), skin (Costello et al 2009;Grice et al 2009), and conjunctiva (Graham et al 2007). While saturation deep sequencing of a complex biome is the theoretical gold standard for its characterization (Venter et al 2004;Williamson et al 2008), such an approach is not yet economical or practical for clinical samples and is very computationally intensive.…”
mentioning
confidence: 99%